Peran Pendidikan Agama Islam dalam Membentuk Kepribadian Remaja (Studi Kasus di Kelurahan Karangrejo Kota Metro) - Ikhwan Aziz Q (Jurnal Al-Hikam, 2022)
Islamic education is sourcing and guiding in human life. Islamic education comes to increase spiritual potency and to make believing to Allah and to make good attitudes. But the existence of Islamic education in modern era is to be sunk especially in adolescents’ soul and adolescents’ thinking and then bring them to Islamic sublimation. Their frailness is increase every time. So they need Islamic teaching education to build their character well. In Islam, education is very important, even, it is said that the essential goal from given holy books, samawi religion and sent the messengers are to give them good education in human life.  There are ways from rosululloh to make adolescents’ character; they are from rosululloh’s sample, demonstration etc. So, they have quality values based on Islamic teaching. The scope of this research is in Karangrejo sub district Metro Utara district Metro City. The objective of this research is to know the goal, material, and method to build the character of adolescents in Karangrejo sub district Metro Utara district Metro city . In this research the researcher used data collection. They are observation, interview and documentation. The result of the character building in Islamic education showed that character building’s function is to make strong belief; the adolescents always do Allah’s direction and leave Allah’s prohibition. They also have good character and attitude. The methods that were used were sample, advice, and punishment. Factors that influenced are family environment, education environment, society environment and the competence that adolescents have. As parent we must be able to raise and lead adolescents’ character. If they have good character from the children they will have strong foundation in their life. So they don’t easily affected by negative character. Then they are already to face modern era. Keywords: Education Character, The Role of Islamic Education, Islamic Education